Media Buku Cerita Mengenai Bentuk-Bentuk Bullying Dalam Kegiatan Bimbingan Klasikal Untuk Peserta Didik Sekolah Dasar - Yunisa Asih Prasetya; Wirda Hanim; Lara Fridani (Indonesian Journal of Learning Education and Counseling, 2020)
The purpose of this study is to find out how the effectiveness of the storytelling method uses storybook media in increasing the knowledge of elementary school students about bullying and the steps in implementation in classical guidance activities. The research method in this article, the author uses the library research method. The results of this study indicate that in an effort to provide information to students in using storybook methods and media there are a number of things that must be the attention of guidance and counseling teachers, namely, the design of service implementation in accordance with students' development tasks, story themes, vocals, expressions , class management, and appropriate use of media. The story gives children the opportunity to express fantasy and explore conflict situations, also allows children to deal with important issues and feelings. So that using an interesting storybook media can optimize student achievement in following classical guidance activities in basic services.